Non-aqueous electrolyte secondary battery

JP7645466B2Active Publication Date: 2025-03-14PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021554166
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-31
Filing Date
2020-09-17
Publication Date
2025-03-14
Estimated Expiration
2040-09-17

Smart Images

  • Figure 0007645466000002
    Figure 0007645466000002
  • Figure 0007645466000001
    Figure 0007645466000001
Patent Text Reader

Abstract

This non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode, and a non-aqueous electrolyte, and during charging, a lithium metal is precipitated in the negative electrode, and during discharging, the lithium metal from the negative electrode is dissolved in the non-aqueous electrolyte. The positive electrode includes a positive electrode mixture containing a positive electrode active material and an additive. The positive electrode active material contains a composite oxide containing lithium and a transition metal. The additive comprises a particulate base material, and an organic compound group fixed by a covalent bond to the surface of the base material. The covalent bond includes an X-O-A bond. An element X is bonded with the organic compound group, and is at least one type selected from the group comprising Si and Ti. An element A is an element constituting the base material. The number of carbon atoms of the organic compound group is 2 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a non-aqueous electrolyte secondary battery. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, typified by lithium ion secondary batteries, have high energy density and high output, and are considered promising as power sources for mobile devices such as smartphones, power sources for vehicles such as electric vehicles, storage devices for natural energy such as solar power, etc. A composite oxide containing lithium and a transition metal is used as the positive electrode active material of non-aqueous electrolyte secondary batteries.

[0003] Meanwhile, with the aim of achieving even higher battery capacity, nonaqueous electrolyte secondary batteries in which lithium metal is deposited on the negative electrode current collector during charging and the lithium metal dissolves during discharging are being considered (e.g., Patent Document 1).

[0004] Patent Document 2 proposes that in a lithium-ion secondary battery, aluminum oxide, the surface of which is partially or entirely covered with carbon, is contained in a positive electrode mixture containing a composite oxide containing lithium, nickel, manganese, and cobalt. Hydrofluoric acid in the electrolyte is captured by the aluminum oxide, the surface of which has many hydroxyl groups, and deterioration of the composite oxide caused by hydrofluoric acid is suppressed. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-243957 A [Patent Document 2] International Publication No. 2016 / 098553 Brochure Summary of the Invention

[0006] When a non-aqueous electrolyte secondary battery is exposed to high temperatures due to an internal short circuit or the like, oxygen is generated from the positive electrode containing a complex oxide. In the battery described in Patent Document 1, oxygen generated from the positive electrode is likely to react with lithium metal deposited on the negative electrode current collector, and the reaction causes the battery to heat up, promoting oxygen generation from the positive electrode and increasing the internal pressure of the battery. In addition, the non-aqueous electrolyte is oxidized and decomposed by the oxygen generated from the positive electrode, which may increase the internal pressure of the battery due to the associated gas generation. The increase in internal pressure of the battery may damage the battery case, and there is a demand for improved battery safety.

[0007] One aspect of the present disclosure relates to a nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, and a nonaqueous electrolyte, in which lithium metal is precipitated on the negative electrode during charging and the lithium metal is dissolved from the negative electrode into the nonaqueous electrolyte during discharging, the positive electrode comprising a positive electrode mixture containing a positive electrode active material and an additive, the positive electrode active material comprising a composite oxide containing lithium and a transition metal, the additive comprising a particulate base material and an organic compound group fixed to a surface of the base material by a covalent bond, the covalent bond comprising an XOA bond, the element X being bonded to the organic compound group and being at least one selected from the group consisting of Si and Ti, the element A being an element constituting the base material, and the organic compound group having 2 or more carbon atoms.

[0008] According to the present disclosure, the safety of non-aqueous electrolyte secondary batteries can be improved. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic perspective view, with a portion cut away, of a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The non-aqueous electrolyte secondary battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, and a non-aqueous electrolyte, and lithium metal is deposited on the negative electrode during charging, and lithium metal is dissolved from the negative electrode into the non-aqueous electrolyte during discharging. The positive electrode includes a positive electrode mixture including a positive electrode active material and an additive. The positive electrode active material includes a composite oxide including lithium and a transition metal. The additive includes a particulate base material and an organic compound group fixed to the surface of the base material by a covalent bond. The covalent bond includes an XOA bond, in which the element X is bonded to the organic compound group and is at least one selected from the group consisting of Si and Ti, the element A is an element constituting the base material, and the number of carbon atoms of the organic compound group is 2 or more.

[0011] When the battery is exposed to high temperatures due to an internal short circuit or the like, oxygen is generated from the positive electrode containing the composite oxide and absorbed by the additive. Specifically, the organic compound group present on the surface of the substrate reacts with oxygen, and the oxygen is consumed. Therefore, the reaction between the oxygen generated from the positive electrode and the lithium metal deposited on the surface of the negative electrode is suppressed, and the generation of oxygen from the positive electrode due to the heat generation of the battery caused by the reaction is suppressed, and the increase in the internal pressure of the battery due to the generation of oxygen from the positive electrode is suppressed. In addition, the oxidative decomposition of the non-aqueous electrolyte due to the oxygen generated from the positive electrode is suppressed, and the increase in the internal pressure of the battery due to the generation of gas associated with the oxidative decomposition is also suppressed. Therefore, damage to the battery case due to the increase in the internal pressure of the battery is suppressed, and the safety of the battery is improved.

[0012] However, when the number of carbon atoms in the organic compound group is one, the reactivity of the organic compound group with oxygen is low, and oxygen absorption by the additive is insufficient. On the other hand, when the number of carbon atoms in the organic compound group is two or more, the organic compound group is easily contacted with oxygen generated from the positive electrode, and oxygen absorption by the additive is efficiently performed. A chain-like hydrocarbon group (such as an alkyl group) having two or more carbon atoms is a hydrophobic functional group, and the hydrocarbon chain can be linearly extended from the substrate surface, effectively increasing the reaction area with oxygen.

[0013] In the additive, the organic compound group is firmly supported on the surface of the substrate via a covalent bond including an XOA bond. Examples of element A include Al, Si, Ti, Mg, and Zr. The covalent bond including an XOA bond has excellent thermal stability and chemical stability, and is also excellent in stability against non-aqueous electrolytes. This allows the additive to stably absorb oxygen. X is preferably Si, because it is advantageous in terms of cost and is easy to introduce functional groups such as organic compound groups.

[0014] The additive has a bond of RXOA on the surface of the substrate, and preferably has a structure represented by the general formula (1): RX(OA)3. In this case, X is preferably Si. R is an organic compound group. When the additive has a structure represented by the general formula (1): RX(OA)3, three covalent bonds are formed between the organic compound group and the substrate, and the organic compound group is firmly fixed to the surface of the substrate.

[0015] The additive having the structure represented by general formula (1) on the surface of the substrate can be easily formed, for example, by using a substrate having many hydroxyl groups on its surface and R-XQ3 to carry out the reaction of the following formula (1a), where Q includes hydroxyl groups, halogen atoms, alkoxy groups, etc., and alkoxy groups include CH3O groups, C2H5O groups, C3H7O groups, etc.

[0016] R-XQ3+3A-OH → RX(OA)3+3HQ (1a) The fact that the organic compound group is immobilized on the surface of the substrate by a covalent bond including an XOA bond can be confirmed, for example, by using a spectroscopic method, such as energy dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FT-IR), or nuclear magnetic resonance (NMR) spectroscopy (measurement nuclides include 1H, 13C, and 29Si).

[0017] The number of carbon atoms in the organic compound group is preferably from 2 to 12, and more preferably from 2 to 5. In this case, the oxygen absorbing effect of the additive is easily obtained.

[0018] The organic compound group is composed of at least carbon atoms and hydrogen atoms, and may contain other atoms other than carbon atoms and hydrogen atoms. Examples of other atoms include oxygen atoms, nitrogen atoms, and sulfur atoms. The organic compound group may contain a carbon-carbon double bond or a triple bond. The organic compound group may contain a chain-like hydrocarbon group, etc. The hydrocarbon group may be linear or branched. The organic compound group may contain at least one selected from the group consisting of an alkyl group, an alkenyl group, and an alkynyl group. The alkyl group includes an ethyl group, a propyl group, a butyl group, etc., and among them, a propyl group is preferable.

[0019] At least one of the hydrogen atoms of the organic compound group may be substituted with a substituent. For example, the hydrogen atom at the end of the alkyl group may be substituted with a substituent. The substituent may include at least one selected from the group consisting of an amino group, a methacryl group, and a thiol group.

[0020] The substrate may be inorganic particles or organic particles. The inorganic particles preferably contain at least one type of particles selected from the group consisting of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, and zirconium oxide. The aluminum oxide includes alumina (Al2O3) and the like. The silicon oxide includes silica (SiO2) and the like. The titanium oxide includes TiO2 and the like. The magnesium oxide includes MgO and the like. The zirconium oxide includes ZrO2 and the like. The inorganic particles may include silica alumina (a composite oxide containing aluminum and silicon) particles.

[0021] Among these, it is more preferable that the inorganic particles include at least one type of particle selected from the group consisting of aluminum oxide, silicon oxide, and silica alumina, from the viewpoint that a large number of hydroxyl groups are usually present on the surface and that covalent bonds including XOA bonds can be formed by the reaction of formula (1a) or the like to easily fix the organic compound groups.

[0022] Among these, from the viewpoints of cost advantage and excellent chemical and thermal stability, it is more preferable that the inorganic particles contain at least one type of particles selected from the group consisting of aluminum oxide and silicon oxide.

[0023] The content of the additive in the positive electrode mixture is preferably 0.1% by mass or more and 10% by mass or less, more preferably 1% by mass or more and 4% by mass or less, based on the total amount of the positive electrode mixture. When the content of the additive in the positive electrode mixture is 0.1% by mass or more based on the total amount of the positive electrode mixture, the additive is sufficiently contained in the positive electrode mixture, and the oxygen absorption effect is easily obtained. When the content of the additive in the positive electrode mixture is 10% by mass or less based on the total amount of the positive electrode mixture, the positive electrode active material is sufficiently secured in the positive electrode mixture, and the capacity of the battery is easily increased.

[0024] In the additive, the atomic ratio A / X of the element A contained in the base material to the element X contained in the covalent bond is, for example, preferably 10 or more and 80 or less, more preferably 15 or more and 50 or less. When A / X is 10 or more, the surface area of ​​the base material is easily ensured, and it is easy to support an organic compound group on the surface of the base material. When A / X is 80 or less, there are enough organic compound groups on the surface of the base material, and it is easy to obtain the oxygen absorption effect.

[0025] The atomic ratio A / X can be determined, for example, by the following method.

[0026] The battery is disassembled and the positive electrode is removed. The positive electrode is washed with a non-aqueous solvent to remove the non-aqueous electrolyte attached to the positive electrode, and the non-aqueous solvent is removed by drying. A positive electrode mixture is collected from the positive electrode and dissolved in a specified acid to obtain a sample solution. Alternatively, an additive may be dissolved in a specified acid to obtain a sample solution. Using the obtained sample solution, the amount of element A and the amount of element X in the sample solution are determined by inductively coupled plasma (ICP) atomic emission spectroscopy, and the atomic ratio A / X is calculated.

[0027] The positive electrode active material includes a composite oxide containing lithium and a metal other than lithium, Me. The metal Me includes at least a transition metal. From the viewpoint of increasing capacity, the transition metal preferably includes at least nickel (Ni). When the composite oxide includes Ni, oxygen is likely to be generated from the positive electrode when the battery is exposed to high temperatures, and therefore, the oxygen absorption effect of the additive is significantly obtained.

[0028] The transition metal may include Ni and at least one element selected from the group consisting of cobalt (Co), manganese (Mn), iron (Fe), copper (Cu), chromium (Cr), titanium (Ti), niobium (Nb), zirconium (Zr), vanadium (V), tantalum (Ta) and molybdenum (Mo).

[0029] The metal Me may include a metal other than a transition metal. The metal other than a transition metal may include at least one selected from the group consisting of aluminum (Al), magnesium (Mg), calcium (Ca), strontium (Sr), zinc (Zn) and silicon (Si). In addition, the composite oxide may further include boron (B) and the like in addition to the metal.

[0030] From the viewpoint of increasing capacity and improving output characteristics, the metal Me preferably contains Ni and at least one selected from the group consisting of Co, Mn and Al, and more preferably contains Ni, Co, Mn and / or Al. When the metal Me contains Co, the phase transition of the composite oxide containing Li and Ni during charging and discharging is suppressed, the stability of the crystal structure is improved, and the cycle characteristics are likely to be improved. When the metal Me contains Mn and / or Al, the thermal stability is improved.

[0031] From the viewpoint of facilitating high capacity, the atomic ratio of Ni to metal Me in the composite oxide: Ni / Me is preferably 0.55 or more and less than 1, more preferably 0.7 or more and less than 1, and even more preferably 0.8 or more and less than 1. When Ni / Me is 0.7 or more, a large amount of oxygen is generated when the battery is exposed to high temperatures, and therefore the oxygen absorption effect of the additive is significantly obtained.

[0032] The composite oxide may have a structure represented by the general formula (2): LiNi 1-x M x O2 (satisfying 0 < x ≤ 0.2, and M is at least one element selected from the group consisting of Co, Al, Ti, Fe, and Mn). When x is greater than 0 and less than or equal to 0.2, the proportion of Ni in the metal other than Li is large, and when the battery is exposed to high temperatures, the amount of oxygen generated is large. Therefore, the oxygen absorption effect by the additive can be significantly obtained. Also, in this case, it is easy to increase the capacity, and the effects of Ni and the element M can be obtained in a well-balanced manner. Note that in LiNiO2, a decomposition reaction that slowly releases oxygen may proceed in a temperature range lower than the temperature at which the battery undergoes thermal runaway. Therefore, compared with the composite oxide represented by the general formula (2), a rapid oxygen generation reaction is less likely to proceed.

[0033] The composite oxide may have a structure represented by the general formula (3): LiNi 1-y-z Co y Al z O2 (0 ≤ y < 0.2, 0 < z ≤ 0.05, and y + z ≤ 0.2). When y, which represents the composition ratio of Co, is greater than or equal to 0 and less than 0.2, it is easy to maintain high capacity and high output, and the stability of the crystal structure during charge and discharge is likely to be improved. When z, which represents the composition ratio of Al, is greater than 0 and less than or equal to 0.05, it is easy to maintain high capacity and high output, and the thermal stability is likely to be improved. (1 - y - z), which represents the composition ratio of Ni, satisfies greater than 0 and less than or equal to 0.8. In this case, the proportion of Ni in the metal other than Li is large, and when the battery is exposed to high temperatures, the amount of oxygen generated is large. Therefore, the oxygen absorption effect by the additive can be significantly obtained. Also, in this case, it is easy to increase the capacity, and the effects of Ni, Co, and Al can be obtained in a well-balanced manner.

[0034] The ratio D1 / D2 of the average particle diameter D1 of the composite oxide to the average particle diameter D2 of the particulate base material is preferably 1.2 or more and 30 or less. The above average particle diameter D1 and average particle diameter D2 refer to the median diameter at which the volume cumulative value is 50% in the volume-based particle size distribution. The above average particle diameter D1 and average particle diameter D2 are obtained by performing particle size distribution measurement by a laser diffraction method. When D1 / D2 is 1.2 or more, a conductive network between the particles of the composite oxide is easily formed in the positive electrode mixture. When D1 / D2 is 30 or less, an additive is appropriately present around the particles of the composite oxide in the positive electrode mixture, and the oxygen absorption effect is easily obtained. D1 / D2 is more preferably 1.4 or more and 10 or less.

[0035] The composite oxide usually contains secondary particles formed by agglomeration of a plurality of primary particles. The average particle size D1 of the composite oxide is, for example, 5 μm or more and 20 μm or less.

[0036] The average particle diameter D2 of the particulate base material is, for example, 1 μm or more and 10 μm or less.

[0037] In a battery in which lithium metal is precipitated on the negative electrode during charging, the open circuit potential (OCV) of the negative electrode when fully charged is, for example, 70 mV or less with respect to lithium metal. When the rated capacity of the battery is C, the fully charged state is a state in which the battery is charged until the state of charge (SOC) is, for example, 0.98×C or more. The OCV of the negative electrode when fully charged may be measured by disassembling a fully charged battery under an argon atmosphere, removing the negative electrode, assembling a cell with lithium metal as the counter electrode, and then measuring the OCV. The nonaqueous electrolyte of the cell may have the same composition as the nonaqueous electrolyte in the disassembled battery, and for example, the nonaqueous electrolyte used in Example 1 described later may be used as a model nonaqueous electrolyte.

[0038] The configuration of the nonaqueous electrolyte secondary battery will be described in detail below.

[0039] (positive electrode) The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer supported on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces. The positive electrode mixture includes a positive electrode active material and an additive as essential components, and may include a binder, a conductive agent, and the like as optional components. N-methyl-2-pyrrolidone (NMP) or the like is used as the dispersion medium.

[0040] Examples of the binder include resin materials such as fluororesins, polyolefin resins, polyamide resins, polyimide resins, acrylic resins, vinyl resins, polyvinylpyrrolidone, polyethersulfone, and rubber materials. Examples of the fluororesins include polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF). Examples of the rubber materials include styrene-butadiene copolymer rubber (SBR). One type of binder may be used alone, or two or more types may be used in combination.

[0041] Examples of the conductive agent include carbon blacks such as acetylene black, conductive fibers such as carbon fibers and metal fibers, and carbon fluoride. The conductive agent may be used alone or in combination of two or more.

[0042] The positive electrode current collector may be, for example, a metal foil. Examples of metals constituting the positive electrode current collector include aluminum (Al), titanium (Ti), alloys containing these metal elements, and stainless steel. The thickness of the positive electrode current collector is not particularly limited, but is, for example, 3 to 50 μm.

[0043] (Negative electrode) The negative electrode may include a negative electrode current collector. In this case, lithium metal is deposited on the surface of the negative electrode current collector during charging, and the lithium metal deposited on the surface of the negative electrode current collector dissolves in the non-aqueous electrolyte during discharging.

[0044] For example, a metal foil can be used for the negative electrode current collector. The metal constituting the negative electrode current collector is preferably a metal that does not react with lithium metal, such as copper (Cu), nickel (Ni), iron (Fe), and alloys containing these metal elements. The thickness of the negative electrode current collector is not particularly limited, and is, for example, 5 μm or more and 300 μm or less.

[0045] The negative electrode may include a negative electrode current collector and a negative electrode mixture layer supported on the surface of the negative electrode current collector. However, from the viewpoint of achieving a high-capacity non-aqueous electrolyte secondary battery, the thickness of the negative electrode mixture layer is set to be thin enough so that lithium metal can be precipitated on the negative electrode during charging. In this case, the design capacity Cn of the negative electrode active material in the negative electrode mixture layer relative to the design capacity Cp of the positive electrode satisfies Cn / Cp<1, and may also satisfy Cn / Cp<0.8. In this case, lithium metal is precipitated on the surface of the negative electrode mixture layer during charging, and the lithium metal precipitated on the surface of the negative electrode mixture layer during discharging dissolves in the non-aqueous electrolyte.

[0046] The negative electrode mixture layer can be formed, for example, by applying a negative electrode slurry in which the negative electrode mixture is dispersed in a dispersion medium to the surface of the negative electrode current collector and drying it. The coating film after drying may be rolled as necessary. The negative electrode mixture layer may be formed on one surface of the negative electrode current collector or on both surfaces. For example, water or NMP is used as the dispersion medium.

[0047] The negative electrode mixture contains a negative electrode active material as an essential component, and may contain optional components such as a binder, a conductive agent, and a thickener. As the binder and conductive agent, those exemplified for the positive electrode can be used. As the thickener, for example, carboxymethylcellulose (CMC) and its modified form (Na salt, etc.) can be mentioned.

[0048] The negative electrode active material may contain a carbon material that absorbs and releases lithium ions. Examples of the carbon material that absorbs and releases lithium ions include graphite (natural graphite, artificial graphite), graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Among them, graphite is preferable because it has excellent charge / discharge stability and a small irreversible capacity.

[0049] The negative electrode active material may include an alloy-based material. The alloy-based material is a material containing at least one metal capable of forming an alloy with lithium, and examples thereof include silicon, tin, silicon alloys, tin alloys, and silicon compounds. The alloy-based material may be a composite material having a lithium ion conductive phase and silicon particles dispersed in the phase. The lithium ion conductive phase may be a silicate phase, a silicon oxide phase containing 95% or more by mass of silicon dioxide, a carbon phase, or the like.

[0050] The negative electrode active material may be a combination of an alloy material and a carbon material. In this case, the mass ratio of the carbon material to the total of the alloy material and the carbon material is, for example, preferably 80 mass % or more, and more preferably 90 mass % or more.

[0051] (Non-aqueous electrolyte) The non-aqueous electrolyte contains lithium ions and anions and has lithium ion conductivity. The non-aqueous electrolyte may be liquid. The liquid non-aqueous electrolyte contains, for example, lithium ions, anions, and a non-aqueous solvent. The liquid non-aqueous electrolyte is prepared by dissolving a lithium salt in a non-aqueous solvent. The lithium salt dissolves in the non-aqueous solvent to generate lithium ions and anions.

[0052] The non-aqueous electrolyte may be in a gel state. The gel non-aqueous electrolyte may contain, for example, lithium ions, anions, and a matrix polymer, and may further contain a non-aqueous solvent. As the matrix polymer, for example, a polymer material that absorbs the non-aqueous solvent and gels is used. Examples of the polymer material include fluororesin, acrylic resin, and polyether resin.

[0053] As the anion, a known anion used in the non-aqueous electrolyte of a lithium secondary battery can be used. Specifically, BF4 - , ClO4 - , PF6 - , CF3SO3 - , CF3CO2 -, anions of imides, anions of oxalate complexes, etc. Examples of anions of imides include N(SO2CF3)2 - , N(C m F 2m+1 SO2) x (C n F 2n+1 SO2)y - (m and n are each independently an integer of 0 or 1 or more, and x and y are each independently 0, 1, or 2, and x+y=2 is satisfied.) The anion of the oxalate complex may contain boron and / or phosphorus. The anion of the oxalate complex may be B(C2O4)2 - , difluorooxalate borate anion: BF2(C2O4) - , PF4(C2O4) - , PF2(C2O4)2 - The anions may be used alone or in combination of two or more.

[0054] From the viewpoint of suppressing lithium metal from being precipitated in a dendritic form, the non-aqueous electrolyte preferably contains at least an anion of an oxalate complex. The interaction between the anion of the oxalate complex and lithium makes it easier for the lithium metal to be precipitated uniformly in the form of fine particles. This makes it easier to suppress localized precipitation of the lithium metal. The anion of the oxalate complex may be combined with another anion. The other anion may be PF 6- and / or the anion of an imide.

[0055] The concentration of the anion in the non-aqueous electrolyte may be 0.5 mol / L or more and 3.5 mol / L or less. The concentration of the anion of the oxalate complex in the non-aqueous electrolyte may be 0.05 mol / L or more and 1 mol / L or less.

[0056] Examples of non-aqueous solvents include esters, ethers, nitriles, amides, and halogen-substituted products thereof. The non-aqueous solvents may be used alone or in combination of two or more. Examples of halogen-substituted products include fluorides.

[0057] Examples of the ester include cyclic carbonate esters, chain carbonate esters, cyclic carboxylate esters, chain carboxylate esters, etc. Examples of the cyclic carbonate esters include ethylene carbonate (EC), propylene carbonate (PC), etc. Examples of the chain carbonate esters include dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. Examples of the cyclic carboxylate esters include γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. Examples of the chain carboxylate esters include ethyl acetate, propyl acetate, methyl propionate (PM), etc.

[0058] Examples of ethers include cyclic ethers and chain ethers. Examples of cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, and 2-methyltetrahydrofuran. Examples of chain ethers include 1,2-dimethoxyethane, diethyl ether, ethyl vinyl ether, and 1,2-diethoxyethane.

[0059] The non-aqueous electrolyte may contain at least one component selected from the group consisting of vinylene carbonate (VC), fluoroethylene carbonate (FEC), and vinyl ethylene carbonate (VEC). When the non-aqueous electrolyte contains the above component, a good coating is formed on the surface of the negative electrode, and the formation of lithium metal dendrites is suppressed.

[0060] (Separator) Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, polyolefin such as polypropylene and polyethylene is preferable.

[0061] An example of the structure of the non-aqueous electrolyte secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and a non-aqueous electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, an electrode group of another form, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween, may be applied. The non-aqueous electrolyte secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.

[0062] FIG. 1 is a schematic perspective view, with a portion cut away, of a prismatic nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure.

[0063] The battery includes a bottomed prismatic battery case 4, and an electrode group 1 and a non-aqueous electrolyte (not shown) housed within the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed between them to prevent direct contact. The electrode group 1 is formed by winding the negative electrode, positive electrode, and separator around a flat plate-shaped winding core and then removing the winding core.

[0064] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6 provided on the sealing plate 5 via a resin insulating plate (not shown). The negative electrode terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the positive electrode lead 2 is connected to the back surface of the sealing plate 5 via an insulating plate. That is, the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive electrode terminal. The insulating plate separates the electrode group 1 and the sealing plate 5, and separates the negative electrode lead 3 and the battery case 4. The periphery of the sealing plate 5 is fitted into the open end of the battery case 4, and the fitting portion is laser welded. In this way, the opening of the battery case 4 is sealed with the sealing plate 5. The injection hole for the non-aqueous electrolyte provided in the sealing plate 5 is closed with a sealing plug 8 .

[0065] <Example> Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.

[0066] Example 1 (1) Preparation of the positive electrode N-methyl-2-pyrrolidone (NMP) was added to the positive electrode mixture and stirred to prepare a positive electrode slurry. The positive electrode mixture was a mixture of a composite oxide (positive electrode active material) containing lithium and a transition metal, an additive, acetylene black (AB), and polyvinylidene fluoride (PVDF). In the positive electrode mixture, the mass ratio of the composite oxide, AB, and PVDF was 100:2:2. The content of the additive in the positive electrode mixture was 2 mass% relative to the total positive electrode mixture. The composite oxide was LiNi 0.90 Co 0.07 Al 0.03 O2 (average particle size D1: 10 μm) was used.

[0067] The additive used was Al2O3 particles (average particle size D2: 5 μm) having propyl groups (C3H7 groups) on the surface as organic compound groups. Specifically, Al2O3 particles having a structure represented by C3H7-Si(OAl)3 on the surface were used. The fixation of C3H7 groups to the surface of the Al2O3 particles via covalent bonds (Si-O-Al) was performed by reacting Al2O3 particles having OH groups on the surface with Si(OCH3)3-C3H7. The atomic ratio Al / Si in the additive was set to 30 by adjusting the amount of Si(OCH3)3-C3H7. The ratio of the average particle size D1 of the composite oxide to the average particle size D2 of the Al2O3 particles: D1 / D2 was 2.

[0068] The positive electrode slurry was applied to the surface of an aluminum foil (thickness 15 μm) serving as a positive electrode current collector, and the coating was dried and then rolled. In this way, a positive electrode mixture layer was formed on both sides of the aluminum foil to obtain a laminate. The laminate was cut to a predetermined size to obtain a positive electrode. In addition, an exposed portion of the positive electrode current collector that does not have a positive electrode mixture layer was formed in a part of the positive electrode. One end of an aluminum positive electrode lead was attached to the exposed portion of the positive electrode current collector by welding.

[0069] (2) Preparation of the negative electrode An electrolytic copper foil (thickness 10 μm) serving as a negative electrode current collector was cut to a predetermined size to form a negative electrode. One end of a nickel negative electrode lead was attached to the negative electrode current collector by welding.

[0070] (3) Preparation of non-aqueous electrolyte A non-aqueous electrolyte was prepared by dissolving LiPF6 and LiBF2(C2O4) in a non-aqueous solvent. The non-aqueous solvent used was a mixed solvent containing fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 20:5:75. The concentration of LiPF6 in the non-aqueous electrolyte was 1.0 mol / L. The concentration of LiBF2(C2O4) in the non-aqueous electrolyte was 0.5 mol / L.

[0071] (4) Fabrication of non-aqueous electrolyte secondary battery A wound electrode group was prepared by winding the positive and negative electrodes with a polyethylene separator interposed therebetween. The electrode group was vacuum-dried and then housed in a battery case that also served as a negative electrode terminal. At this time, an upper insulating plate and a lower insulating plate made of resin were arranged above and below the electrode group, respectively. A bottomed cylindrical iron case (outer diameter 21 mm, height 70 mm) was used as the battery case. Next, a non-aqueous electrolyte was injected into the battery case, and then the opening of the battery case was closed using a metal sealing body that also served as a positive electrode terminal. At this time, a resin gasket was interposed between the sealing body and the open end of the battery case. The other end of the positive electrode lead was connected to the sealing body, and the other end of the negative electrode lead was connected to the inner bottom surface of the battery case. In this way, a 21700-type cylindrical non-aqueous electrolyte secondary battery A1 was prepared.

[0072] Example 2 A battery A2 was produced in the same manner as in Example 1, except that the content of the additive in the positive electrode mixture was 4 mass % based on the total mass of the positive electrode mixture.

[0073] Comparative Example 1 A battery B1 was produced in the same manner as in Example 1, except that no additive was added to the positive electrode mixture.

[0074] Comparative Example 2 Al2O3 particles were used as they were as additives. The content of Al2O3 particles in the positive electrode mixture was 4 mass% based on the total amount of the positive electrode mixture. Other than the above, battery B2 was produced in the same manner as in Example 1. Al2O3 particles usually have many hydroxyl groups on the surface.

[0075] Comparative Example 3 The additive used was Al2O3 particles having a methyl group (CH3 group) on the surface. Specifically, Al2O3 particles having a structure represented by CH3-Si(OAl)3 on the surface were used. The CH3 group was fixed to the surface of the Al2O3 particles via a covalent bond (Si-O-Al) by reacting Al2O3 particles having an OH group on the surface with Si(OCH3)3-CH3. The content of the additive in the positive electrode mixture was 4 mass% with respect to the entire positive electrode mixture. Battery B3 was produced in the same manner as in Example 1 except for the above.

[0076] Comparative Example 4 The additive used was Al2O3 particles whose surface was coated with carbon. The Al2O3 particles whose surface was coated with carbon were obtained by mixing Al2O3 particles and polyvinyl alcohol powder in a mass ratio of 100:70 and baking at 850°C for 1 hour in a nitrogen atmosphere. The content of the additive in the positive electrode mixture was 4 mass% with respect to the entire positive electrode mixture. Battery B4 was produced in the same manner as in Example 1 except for the above.

[0077] 《Reference example 1》 (1) Preparation of the negative electrode Water was added to the negative electrode mixture and stirred to prepare a negative electrode slurry. The negative electrode mixture was a mixture of artificial graphite (average particle size 25 μm), styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC-Na). In the negative electrode mixture, the mass ratio of artificial graphite to SBR and CMC-Na was 100:1:1.

[0078] The negative electrode slurry was applied to the surface of the copper foil, the coating was dried, and then rolled to obtain a laminate in which a negative electrode mixture layer was formed on both sides of the copper foil. The laminate was cut to a predetermined size to prepare a negative electrode.

[0079] (2) Preparation of non-aqueous electrolyte A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.2 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1).

[0080] The negative electrode and non-aqueous electrolyte obtained above were used. No additive was added to the positive electrode mixture.

[0081] Other than the above, a battery C1 was produced in the same manner as in Example 1. The thickness of the negative electrode mixture layer was adjusted so that Li metal would not precipitate on the surface of the negative electrode during charging. That is, the design capacity Cn of the negative electrode carried by the negative electrode active material in the negative electrode mixture layer was made larger than the design capacity Cp of the positive electrode.

[0082] The following evaluations were carried out on the batteries A1 to A2, B1 to B4, and C1.

[0083] [Evaluation: Measurement of gas generation rate] The batteries obtained above were charged at a constant current of 0.1 C in an environment of 25° C. until the voltage reached 4.3 V, and then charged at a constant voltage of 4.3 V until the current reached 0.01 C. In this manner, fully charged batteries were obtained. In the batteries A1 to A2 and B1 to B4, Li metal was precipitated on the surface of the negative electrode current collector by charging. In the battery C1, lithium ions were absorbed into the graphite in the negative electrode mixture by charging.

[0084] A fully charged battery was placed in a sealed container, and an internal short circuit was caused in the battery by piercing it with a nail, causing the battery to heat up. At this time, the change over time in the amount of gas generated from the battery was measured. The amount of gas generated from the battery was calculated by measuring the pressure P in the sealed container with a pressure sensor, measuring the temperature T in the sealed container with a thermocouple, and using the gas state equation: PV=nRT (V is the volume in the sealed container, n is the amount of gas, and R is the gas constant). Based on the measurement results, the maximum amount of gas generated per unit time was calculated and used as the gas generation rate. The gas generation rate was expressed as an index with the gas generation rate in the case of battery B1 of Comparative Example 1 taken as 100.

[0085] The evaluation results are shown in Table 1.

[0086] [Table 1]

[0087] In the batteries A1 and A2 of Examples 1 and 2, the gas generation rate was slower and the increase in the internal pressure of the battery was suppressed, as compared with the batteries B1 to B4 of Comparative Examples 1 to 4.

[0088] In battery B1 of Comparative Example 1, in which Li metal was precipitated on the negative electrode current collector during charging, the gas generation rate was significantly increased and the internal battery pressure was significantly increased compared to battery C1 of Reference Example 1, in which Li ions were absorbed into the graphite in the negative electrode mixture during charging. [Industrial Applicability]

[0089] The nonaqueous electrolyte secondary battery according to the present disclosure is suitable for use, for example, as a power source for mobile devices such as smartphones, a power source for vehicles such as electric cars, and a storage device for natural energy such as solar power. [Explanation of symbols]

[0090] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing

Claims

1. A positive electrode, a negative electrode, and a non-aqueous electrolyte, A non-aqueous electrolyte secondary battery in which lithium metal is precipitated on the negative electrode during charging, and the lithium metal is dissolved from the negative electrode into the non-aqueous electrolyte during discharging, The positive electrode includes a positive electrode mixture including a positive electrode active material and an additive, The positive electrode active material includes a composite oxide including lithium and a transition metal, The additive comprises a particulate substrate and an organic compound group fixed to a surface of the substrate via a covalent bond including an X-O-A bond; The element X is at least one selected from the group consisting of Si and Ti, The element A is an element constituting the base material, The organic compound group has 2 or more carbon atoms.

2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the organic compound group has 2 or more and 12 or less carbon atoms.

3. The nonaqueous electrolyte secondary battery according to claim 2 , wherein the number of carbon atoms is 2 or more and 5 or less.

4. 4. The nonaqueous electrolyte secondary battery according to claim 1, wherein the organic compound group includes at least one selected from the group consisting of an alkyl group, an alkenyl group, and an alkynyl group.

5. At least one hydrogen atom of the organic compound group is substituted with a substituent; 5. The nonaqueous electrolyte secondary battery according to claim 1, wherein the substituent comprises at least one selected from the group consisting of an amino group, a methacryl group, and a thiol group.

6. The additive is, on the surface of the base material, a compound represented by the general formula (1): R-X(OA) 3 The structure is represented by 6. The nonaqueous electrolyte secondary battery according to claim 1, wherein in the general formula (1), R is the organic compound group.

7. 7. The nonaqueous electrolyte secondary battery according to claim 1, wherein the transition metal includes at least nickel.

8. The composite oxide has the general formula (2): LiNi 1-x M x O 2 The structure is represented by 8. The nonaqueous electrolyte secondary battery according to claim 7, wherein in said general formula (2), 0<x≦0.2 is satisfied, and M is at least one element selected from the group consisting of Co, Al, Ti, Fe, and Mn.

9. The composite oxide has the general formula (3): LiNi 1-y-z Co y A z O 2 The compound has a structure represented by 8. The nonaqueous electrolyte secondary battery according to claim 7, wherein, in said general formula (3), 0≦y<0.2, 0<z≦0.05, and y+z≦0.2 are satisfied.

10. The substrate comprises inorganic particles, 10. The nonaqueous electrolyte secondary battery according to claim 1, wherein the inorganic particles include at least one type of particles selected from the group consisting of aluminum oxide, silicon oxide, titanium oxide, magnesium oxide, and zirconium oxide.

11. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 10, wherein the content of the additive in the positive electrode mixture is 0.1 mass% or more and 10 mass% or less with respect to the entire positive electrode mixture.

12. The non-aqueous electrolyte contains lithium ions and anions, The nonaqueous electrolyte secondary battery according to any one of claims 1 to 11, wherein the anion includes an anion of an oxalate complex.

13. The nonaqueous electrolyte secondary battery according to claim 12 , wherein the anion of the oxalate complex includes a difluorooxalatoborate anion.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2001243957A

  • Composite binder for battery, and anode and lithium battery including the same

    JP2013165061A

  • Electrode material for lithium ion secondary battery, manufacturing method of the electrode material and lithium ion secondary battery

    JP2014099295A

  • Power-storage device

    JP2015109227A

  • Slurry composition and method of manufacturing positive electrode for lithium ion secondary battery

    JP2017027768A